Amping-up pedagogy through interdisciplinary instruction: A study of the effects of interdisciplinary instruction on undergraduate attitudes and values related to energy issues at the U.S. naval academy - Caton, Patrick; Ernst, Howard; Flack, Karen; Smith, Joseph P.; Swope, Kurtis (Journal of Interdisciplinary Studies in Education, 2017)
This study makes use of a pre-test/post-test design (with a control group) to test the effect of an interdisciplinary energy course on student attitudes and values related to energy issues. The interdisciplinary energy course was co-taught by engineering, political science, economics, and oceanography professors at the United States Naval Academy during the fall of 2015. The study finds that students in the interdisciplinary energy course experienced significant changes in their energy attitudes on half the categories tested, while students in the control group did not experience similar changes. The changes were greatest among female students, politically moderate students, and engineering students. The findings suggest that interdisciplinary instruction can have a powerful impact on student values, but that the impact works through existing demographic and ideological factors.